Internet Gaming Disorder Symptom Severity and Mental Health Correlates among Young Adults in Western India: A Cross-sectional Analysis - Chintan Bhaveshkumar Panchal; Harshad Rameshbhai Dudhagara; Mehul J. Brahmbhatt (Annals of Indian Psychiatry, 2026)
Abstract Background: Research on internet gaming disorder (IGD) has predominantly relied on binary diagnostic thresholds, which do not capture the subclinical, dose-dependent burden of gaming-related psychopathology. Data from Indian populations employing dimensional, severity-based methods are limited. Aims: To examine the independent association of continuous IGD symptom severity with depression, anxiety, and sociooccupational functioning in a nonclinical sample of Indian young adults. Materials and Methods: A cross-sectional study was conducted among young adults aged 18–30 years in Gujarat, India ( n = 359). Gaming severity was measured using the IGD scale 9–short form, depression using the beck depression inventory, anxiety using the Generalized Anxiety Disorder-7, and functioning using a self-rated Global Assessment of Functioning proxy. Multiple linear regression was performed with bootstrap validation (5000 resamples). Cohen’s f 2 effect sizes and post hoc power were computed. Results: The prevalence of clinical IGD was 1.1% ( n = 4). Gaming severity was significantly associated with depression ( r = 0.362, 95% confidence interval [CI]: 0.240–0.482), anxiety ( r = 0.305, 95% CI: 0.192–0.420) and impaired functioning ( r = −0.198, 95% CI: −0.326 to −0.070). In adjusted regression, gaming severity independently predicted depression ( B = 0.62, 95% CI: 0.44–0.81, f 2 = 0.184) and anxiety ( B = 0.27, 95% CI: 0.19–0.36, f 2 = 0.149); both P < 0.001. Conclusions: In Indian young adults, subclinical gaming severity was independently associated with depression and anxiety. The findings support the use of dimensional, severity-based screening rather than binary diagnostic thresholds alone.